The Path-Goal Theory of Leadership: A Partial Test and Suggested Refinement - Stinson, John E.; Johnson, Thomas W. (Academy of Management Journal, 1975)
Hypotheses derived from the path-goal theory of leadership were tested. Data were obtained from military officers. Civil Service personnel, and project engineers. Results supported the theory with respect to consideration, but tended to counter the theory regarding initiating structure. An extension of the path-goal theory is suggested.